2021
DOI: 10.3390/biology10121228
|View full text |Cite
|
Sign up to set email alerts
|

Co-Existence of Free-Living Amoebae and Potential Human Pathogenic Bacteria Isolated from Rural Household Water Storage Containers

Abstract: This study investigated the co-existence of potential human pathogenic bacteria and free-living amoebae in samples collected from stored water in rural households in South Africa using borehole water as a primary water source. Over a period of 5 months, a total of 398 stored water and 392 biofilm samples were collected and assessed. Free-living amoebae were identified microscopically in 92.0% of the water samples and 89.8% of the biofilm samples. A further molecular identification using 18S rRNA sequencing ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
2
3
0
1
Order By: Relevance
“…In contrast, the Naegleria isolates had a broad distribution in water and soil along the different natural ecosystems sampled ( Table 1 ). Our results are in line with several previous studies that analyzed the diversity of FLA in rivers ( 51 ), rural borehole water ( 75 ), drinking-water processing plants ( 53 , 76 ), domestic and clinical tap water distribution systems ( 54 , 77 79 ), public baths ( 56 ), and swimming pools ( 80 , 81 ). These publications report a high prevalence of V. vermiformis in these aquatic, mostly human-made ecosystems.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the Naegleria isolates had a broad distribution in water and soil along the different natural ecosystems sampled ( Table 1 ). Our results are in line with several previous studies that analyzed the diversity of FLA in rivers ( 51 ), rural borehole water ( 75 ), drinking-water processing plants ( 53 , 76 ), domestic and clinical tap water distribution systems ( 54 , 77 79 ), public baths ( 56 ), and swimming pools ( 80 , 81 ). These publications report a high prevalence of V. vermiformis in these aquatic, mostly human-made ecosystems.…”
Section: Discussionsupporting
confidence: 92%
“…This finding aligns with prior studies that have revealed a higher prevalence of the FLA in areas characterised by elevated levels of organic matter contamination [36][37][38]. Additionally, the formation of biofilms inside piped water systems is also major contribution in the survival and transmission of FLA [39][40][41].…”
Section: Discussionsupporting
confidence: 91%
“…Recent study has reported that Vermamoeba (Hartmannella) vermiformis as the etiological agent of an infection close to the eye of a female patient [5]. Some investigators checked localization of FLAs in our environments because they thought that FLA is a potential pathogen or vector of bacterial pathogens [33][34][35][36]. FLAs were detected with potential human pathogenic bacteria in stored water in rural households in South Africa [34].…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators checked localization of FLAs in our environments because they thought that FLA is a potential pathogen or vector of bacterial pathogens [33][34][35][36]. FLAs were detected with potential human pathogenic bacteria in stored water in rural households in South Africa [34]. Several bacteria are ingested by FLAs and digested as a food source, whereas others have adapted to survive and grow within the amoebae by resisting against FLA, which are known as amoeba-resistant bacteria [2].…”
Section: Discussionmentioning
confidence: 99%